Analysis of the Health Service Quality and Service Innovation of Dokter Muter on Patient Satisfaction - Amellia Reikatiffany; Sugiyanta Sugiyanta; Dodi Wijaya (GLOBAL HEALTH SCIENCE GROUP, 2025)
Dokter Muter (Near by Doctors and other health workers through integrated services) is an innovation of the Lumajang District Health, Population Control and Family Planning Office (Dinkes P2KB). This innovation aims to bring access to health services closer to remote or geographically challenging areas. The purpose of this study was to determine the effect of health service quality and the Doctor Muter service innovation on patient satisfaction in Lumajang District. The population of this study were patients who had received or were receiving Dokter Muter services in 25 health centers. The data collection method was a questionnaire using Likert scale. This study used a cross-sectional design with proportional stratified random sampling technique. The number of samples in this study was 384 respondents. Data analysis was done using path analysis. Based on the results of the study, it is known that the path coefficient value of service quality on patient satisfaction β = 0.234 is positive with a p-value of 0.000, so that service quality has an influence on patient satisfaction. The path coefficient value of Dokter Muter’s service innovation on patient satisfaction β = 0.639 is positive with a p-value of 0.000, so Dokter Muter's service innovation has an influence on patient satisfaction. The R-squared value for the patient satisfaction variable is 0.707, which means that 70.7 percent of the patient satisfaction variable is influenced by Dokter Muter's service quality and service innovation, and the remaining 29.3 percent is influenced by constructs outside the model.